Evaluating the Correlation Between Thoracic Ultrasound and Thoracic Computed Tomography Scores of Patients with Severe COVID-19 Pneumonia Receiving Intensive Care - Ayşe Vahapoğlu; Döndü Genç Moralar; Ferhat Çengel; Zuhal Çavuş; Ülkü Aygen Türkmen (Galenos Yayinevi, 2021)
Objective:The coronavirus disease-2019 (COVID-19) pandemic has turned into a global health issue in a short time because of its increasing mortality and high infection rate. Since thoracic computed tomography (CT) cannot be performed and it is not possible to transfer COVID-19 patients followed-up in the intensive care unit (ICU), follow-up, and diagnosis using lung ultrasound (LUS) has been highly advantageous nowadays. The aim of this study was to assess the correlation between the thoracic CT score and LUS score and to determine their association with mortality.Materials and Methods:Patients admitted to the ICU, diagnosed to have COVID-19 pneumonia, underwent an initial thoracic CT examination and who underwent LUS during admission to the ICU were included in the study. The clinical parameters, demographic characteristics, prognosis, LUS, and thoracic CT scores of the patients were recorded prospectively. The survivors and deceased patients' demographic characteristics were compared.Results:The mean age of the 29 patients included in this study was 61.93±14.21 years, and the male-to-female ratio was 18/11 (62.1%/37.9%). A strong positive correlation was between the thoracic CT score and LUS score (r=0.964; p<0.001). The thoracic CT and LUS scores of the survivors were 15.5±2.7 and 27.3±4.9, respectively, while those of the deceased patients were 14.1±3.4 and 25.6±5.8, respectively, and the two groups found no significant difference.Conclusion:A strong positive correlation was found between the thoracic CT score and LUS score of COVID-19 patients admitted to the ICU. This result shows that LUS is easily preferred for patients who require imaging for diagnosis and follow-up under intensive care conditions. The mortality rates of COVID-19 patients could not be predicted by either thoracic CT score or LUS score.